Mapping Global Perspectives: Cyberlaw's Impact on Motorcycle Safety - Masruroh, Tri Antika; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article explores the nexus of cyberlaw and motorcycle safety through an analysis of scholarly articles retrieved from lens.org. Employing keywords "cyberlaw" and "motorcycles," focused on legal journals, the study presents critical safety metrics for riders, the influence of road design on accidents, and the pivotal role of helmets in reducing head injuries. Results underscore the global significance of helmet usage and road safety measures, particularly in developing nations. This comprehensive overview serves as a valuable resource for scholars and students delving into this specialized field, providing access to vital research via lens.org. Highlights: Research Focus: Explores cyberlaw's impact on motorcycle safety. Insights: Highlights critical safety metrics, road design's role in accidents, and the importance of helmets in injury reduction. Global Significance: Emphasizes the crucial need for helmet usage and safety measures, especially in developing countries. Keywords: Cyberlaw, Motorcycles, Helmet Usage, Safety Metrics, Global Perspectives